صور القسم في القرآن الكريم : دراسة موضوعية - Norwardatun binti Mohamed Razali (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
This study deals with several forms of al-qasam (the oath) in the Qur'an. The aim of this study is to give a clear explanation of the oath particularly in terms of its form in the Qur'an as well as its general effects. This study used two methods; the inductive method and the analytical method. The inductive method was used to search the Qur'anic verses that are related to al-qasam (the oath) and its forms. Through this method the study searched for the meaning of al-qasam (the oath) by refering to Arabic language books, Arabic dictionaries (mu'jam) and also jurisprudence books. The analytical method was used thematically on the collection of tafsir particularly and the book of ahkam al-Qur'an. This study concludes that there are three main forms of al-qasam (the oath) in the Qur'an; the first form is al-Yamiin al-Mun'aqadah and its subform is al-iila'. The second form is al-Yamin Ghair al-Mun'aqadah and it subforms are al-laghw and al-ghamuus. The third form is al-Yamin allati laa kaffarah laha and it subforms are al-li'an and al-qasam (the oath) that used to prove justice. This study demonstrates the glory of the Qur'an and its ability to solve problems in society in terms of the implementation of the oath. This study describes the different types of oath in society and what is related to it, starting from relationship problems between couples (husband and wife) in order to protect the woman's right, and lastly to expose the effects of different kinds of oath to the economic and political problems. This study also identifies the importance of the oath in terms of its ability to bring peace among society through its method, its synonym and its different types of phrases despite the same root words. Hence, the benefit from this finding can be gained by the individual as well as the society, for this knowledge comes from the Qur'an which is authentic in terms of its methodology and its sources.